FRI0449 MANAGEMENT AND OUTCOME OF SEPTIC ARTHRITIS OF NATIVE JOINT: A NATIONWIDE SURVEY. (13th June 2020) - Richebé, P.; Godot, S.; Coiffier, G.; Guggenbuhl, P.; Mulleman, D.; Couderc, M.; Dernis, E.; Deprez, V.; Salliot, C.; Urien, S.; Brault, R.; Ruyssen-Witrand, A.; et al.
Abstract : Background: Objectives: To describe current management and outcome of septic arthritis on native joint in French rheumatology departments. Methods: Retrospective, nation-wide multicentric study. 127 French rheumatology departments were contacted to report 10 successive cases of septic arthritis on native joint that occurred between the 01/01/16 to 31/12/17 (excluding mycobacteria). Characteristics, diagnosis procedure, therapeutic management and outcome were recorded. Results: 52 centers included 363 patients (mean age 64± 18.7 years, mean Charlson comorbidity index 4±3). 28.3% patients had a preexisting arthropathy on affected joint. Monoarthritis was observed in 89.6% patients, knee was the most frequent site (38.9%). The most frequent pathogens were Staphylococcus sp (50.7%) and Streptococcus sp. (23.3%). Bacteremia was found in 156 (45.1%) patients and endocarditis in only 12 (3.0%). Management was heterogeneous. All patients received antibiotics for a mean duration of 46.7±22 days (including intravenous route: 17.3±15.4 d). An initial monotherapy was administered in 42.3% of patients. Surgical procedure (mostly lavage 70.6%) was performed in 171 (48.3%), joint immobilization in 128 (35.3%) (median duration of 21.7±14.1 days). 94 (29.2%) patients have had serious complications including 29 (9.5%) death. Factors associated with death are reported in the table. Conclusion: This study shows that management of septic arthritis is very heterogenous with a still high rate of morbidity and mortality. We identified age, comorbidities, bacteremia and recent antibiotherapy were associated with mortality. Of note, duration of antibiotics was not. Thus, new guidelines are needed in order to facilitate septic arthritis management. Disclosure of Interests: Pauline Richebé: None declared, Sophie Godot: None declared, Guillaume Coiffier: None declared, Pascal GUGGENBUHL: None declared, Denis Mulleman: None declared, Marion Couderc: None declared, Emmanuelle Dernis Speakers bureau: Lilly, Novartis, Valentine Deprez: None declared, Carine Salliot: None declared, Saik Urien: None declared, Rachel Brault: None declared, Adeline Ruyssen-Witrand Grant/research support from: Abbvie, Pfizer, Consultant of: Abbvie, BMS, Lilly, Mylan, Novartis, Pfizer, Sandoz, Sanofi-Genzyme, Emmanuel Hoppe: None declared, Jacques-Eric Gottenberg Grant/research support from: BMS, Pfizer, Consultant of: BMS, Sanofi-Genzyme, UCB, Speakers bureau: Abbvie, Eli Lilly and Co., Roche, Sanofi-Genzyme, UCB, Christian Roux: None declared, Sebastien Ottaviani: None declared, Maxime Breban: None declared, Marie Beaufrere: None declared, Alexia Michaut: None declared, Loic Pauvele: None declared, Christelle Darrieutort: None declared, Daniel Wendling: None declared, Pascal COQUERELLE: None declared, Géraldine Bart: None declared, Elisabeth Gervais: None declared, Vincent Goeb: None declared, Marc Ardizzone: None declared, Edouard Pertuiset: None declared, Sophie Derolez: None declared, Jean Marc Ziza: None declared, René-Marc Flipo Consultant of: Johnson and Johnson, MSD France, Novartis, Sanofi, Speakers bureau: Johnson and Johnson, MSD France, Novartis, Sanofi, Raphaèle Seror Consultant of: BMS UCB Pfizer Roche